Afro-vegan : farm-fresh African, Caribbean & Southern flavors remixed - Terry, Bryant, 1974- (Ten Speed Press, 2014)
"A groundbreaking cookbook from beloved chef-activist Bryant Terry, drawing from African, Afro-Caribbean, and Southern food to create over 100 enticing vegan dishes. Rising star chef and food activist Bryant Terry is known for his simple, creative, and delicious vegan dishes inspired by African American cooking. In this landmark cookbook, he remixes foods of the African diaspora to create exciting and approachable recipes such as Corn Maque Choux-Stuffed Jamaican Patties with Hot Pepper Sauce, Berebere-Spiced Black-Eyed Pea Sliders, Crispy Teff-Grit Cakes with Eggplant, Tomatoes, and Peanuts, and Groundnut Stew with Winter Vegetables and Cornmeal Dumplings. He also explores key African ingredients that are popular in Caribbean and Southern dishes--like okra--tracing their history and giving them cultural context. Afro-Vegan will delight Bryant Terry fans; vegans looking for exciting new recipes; cooks interested in African, Afro-Caribbean, and Southern cuisine; and health- and eco-conscious eaters"--